Fairy lies - Baker, E. D. (Bloomsbury, 2012)
Half-fairy Tamisin and her boyfriend, Jak, have been arguing over whether she should return to the land of the fey when Oberon, king of the fairies, kidnaps her and Jak must return to that place of fairies, goblins, and sphinxes to rescue her.